The Relationship Between Healthy Lifestyle and Hospital Utilization Among Adults With Diabetes: Results From a National Cohort in Taiwan. (April 2015) - Li, Chia-Lin; Sheu, Ji-Tian; Wang, Ting-Ann; Wen, Yu-Ping; Chao, Minston; Chang, Hsing-Yi
The aim of this study was to investigate whether adopting healthy lifestyle habits, such as engaging in leisure time physical activity (LTPA), adopting recommended dietary patterns, and not smoking, are associated with reduced hospitalizations over 1 year among adults with diabetes. We analyzed data from a national sample of people aged 18 years and above with self-reported physician-diagnosed diabetes (n = 664) through linkage to the 2001 National Health Interview Survey in Taiwan and the 2002 National Health Insurance claims data. Multivariate analysis showed that participants reporting greater than 150 min/wk of moderate-intensity activity had a significantly lower chance for hospitalization (odds ratio = 0.52; 95% confidence interval [CI] = 0.27-0.98), fewer admissions (incidence rate ratio [IRR] = 0.58; 95% CI = 0.33-1.00), and fewer hospital bed days (IRR = 0.42; 95% CI = 0.20-0.92) compared with inactive individuals. Diet control and smoking status did not significantly predict hospital use after controlling for other factors. Our findings indicate that increased LTPA results in reduced hospitalization among adults with diabetes.